Pengaruh Emotional Intelligence dan Perceived Social Support terhadap Job Search Self-Efficacy - Ardy Wiratama; Prayuda Nur Rifki (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2024)
Generation Z adolescents in Pekalongan Regency, particularly those facing challenges in finding employment, require high levels of emotional intelligence and social support to build job search self-efficacy. The ability to understand and manage their own emotions, along with receiving support from their surroundings, is essential for coping with job search difficulties. A lack of emotional intelligence and social support can increase stress and hinder their job search self-efficacy. This study aims to examine how emotional intelligence and perceived social support affect job search self-efficacy among Generation Z adolescents. The population of this study consisted of teenagers living in Pekalongan Regency, with a sample of 116 adolescents aged 18-30 years, selected using a saturated sampling technique. A Likert scale was used to measure the variables, and regression analysis was employed to analyze the data. The results showed that the F-count value was 194.006, which is greater than the F-table value of 3.08, indicating that the hypothesis was accepted. This means that both emotional intelligence and perceived social support have a significant impact on job search self-efficacy. The study emphasizes the importance of emotional intelligence and social support in enhancing job search self-efficacy, and it suggests that addressing these factors can help Generation Z adolescents overcome the challenges they face in the competitive job market. Therefore, it is recommended that efforts be made to develop emotional intelligence and social support systems for adolescents to improve their job search outcomes.